Top Ten. Diez años de investigación española en Biblioteconomía y Documentación (1996-2006). Ranking e índice h de los 10 autores en activo más citados - Salvador Bruna, Javier (Revista General de Información y Documentación, 2008)
Through the quantitative citation analysis of the ten most active researchers in the Spanish Information Sciences field during the period 1996-2006, the most important publications and topics are described. Comparing the figures of each individual author with the average number of cites received by the top ten researchers, the evolution over time of the authors’ impact is analysed, describing the most important topics and issues published.